Effects of hypercapnia in sepsis: A scoping review of clinical and pre‐clinical data. Issue 4 (27th December 2020) - Clyde, Thomas P.; Coletta, Michael; Jones, Christopher W.; Kilgannon, Hope; Fuller, Brian M.; Trzeciak, Stephen; Roberts, Brian W.
Abstract : Background: Perform a scoping review of (1) pre‐clinical studies testing the physiological effects of higher PaCO2 levels in the setting of sepsis models and (2) clinical investigations testing the effects of hypercapnia on clinical outcomes in mechanically ventilated patients with sepsis. Methods: We performed a search of CENTRAL, PUBMED, CINAHL, and EMBASE. Study inclusion criteria for pre‐clinical studies were: (1) bacterial sepsis model (2) measurement of PaCO2, and (3) comparison of outcome measure between different PaCO2 levels. Inclusion criteria for clinical studies were: (1) diagnosis of sepsis, (2) receiving invasive mechanical ventilation, (3) measurement of PaCO2, and (4) comparison of outcomes between different PaCO2 levels. We performed a qualitative analysis to collate and summarize the physiological and clinical effects of hypercapnia according to the recommended methodology from the Cochrane Handbook. Results: Fifteen pre‐clinical and nine clinical studies were included. Among pre‐clinical studies, the individual studies found higher PaCO2 augments tissue blood flow and oxygenation, and attenuates inflammation and lung injury; however, all pre‐clinical studies were found to have some degree of risk of bias. Six of the nine clinical studies were deemed to be good quality. Among clinical studies hypercapnia was associated with increased cerebral perfusion and oxygenation; however, there were conflicting results testing the association between hypercapnia and mortality. Conclusion: While individual pre‐clinical studies identified potential mechanisms by which changes in PaCO2 levels could affect pathophysiology in sepsis, there is a paucity of clinical data as to the optimal PaCO2 range, demonstrating a need for future research. Registration: PROSPERO number CRD42018086703.